Dyselectrolytemia in under-five children with acute diarrhoea-induced dehydration: a cross-sectional study in a South-East Nigerian hospital - Ezuruike, Ezinwa Olekaibenma; Ibeneme, Chikaodili Adaeze; Uwaezuoke, Samuel Nkachukwu (International Journal of Contemporary Pediatrics, 2022)
Background: Diarrhoeal disease contributes significantly to preventable deaths among under-fives globally. Associated dyselectrolytemia is a major contributor to morbidity and mortality in these children. The aim of the study was to determine the prevalence and pattern of serum electrolyte derangement among under-fives with dehydration due to acute diarrhoea. Methods: It was a hospital-based descriptive cross-sectional study conducted at the Federal Medical Centre, Umuahia involving 150 under-five children with dehydration due to acute diarrhoea from October 2018 to January, 2020. Clinical detail and degree of dehydration were recorded. The serum electrolytes were estimated using Ion selective electrode method. Results: The overall prevalence of electrolyte derangement was 62.6%. Hyponatraemia was the commonest electrolyte derangement, accounting for 31.3% of cases. Hypokalaemia and metabolic acidosis occurred in 24% and 12.7% of cases respectively. Across the different degrees of dehydration hyponatremia was 5 times more likely to develop in the severely dehydrated (OR 5.25, p=0.001) compared to the mildly dehydrated. The odds of developing hypokalaemia were 17 times more likely in the moderately dehydrated (OR 17.21, p=0.007) and 38 times more likely in the severely dehydrated Subjects (OR 38.50, p≤0.001). Conclusions: The frequency of electrolyte derangements was high and increased with the increasing severity of dehydration. Routine estimation of serum electrolytes is advocated for under-five children with acute diarrhoea, especially with moderate and severe dehydration. Also, the use of sodium and potassium-containing fluids can be instituted as choice fluids in resource-poor settings without laboratory support. Background: Diarrhoeal disease contributes significantly to preventable deaths among under-fives globally. Associated dyselectrolytemia is a major contributor to morbidity and mortality in these children. The aim of the study was to determine the prevalence and pattern of serum electrolyte derangement among under-fives with dehydration due to acute diarrhoea. Methods: It was a hospital-based descriptive cross-sectional study conducted at the Federal Medical Centre, Umuahia involving 150 under-five children with dehydration due to acute diarrhoea from October 2018 to January, 2020. Clinical detail and degree of dehydration were recorded. The serum electrolytes were estimated using Ion selective electrode method. Results: The overall prevalence of electrolyte derangement was 62.6%. Hyponatraemia was the commonest electrolyte derangement, accounting for 31.3% of cases. Hypokalaemia and metabolic acidosis occurred in 24% and 12.7% of cases respectively. Across the different degrees of dehydration hyponatremia was 5 times more likely to develop in the severely dehydrated (OR 5.25, p=0.001) compared to the mildly dehydrated. The odds of developing hypokalaemia were 17 times more likely in the moderately dehydrated (OR 17.21, p=0.007) and 38 times more likely in the severely dehydrated Subjects (OR 38.50, p≤0.001). Conclusions: The frequency of electrolyte derangements was high and increased with the increasing severity of dehydration. Routine estimation of serum electrolytes is advocated for under-five children with acute diarrhoea, especially with moderate and severe dehydration. Also, the use of sodium and potassium-containing fluids can be instituted as choice fluids in resource-poor settings without laboratory support.